Heteroaryl bismuthines: a novel synthetic concept and metal⋯π heteroarene interactions12. Issue 25 (15th June 2017) - Preda, A. M.; Schneider, W. B.; Rainer, M.; Rüffer, T.; Schaarschmidt, D.; Lang, H.; Mehring, M.
Abstract : We report a new synthetic route for heteroaryl bismuth compounds, formed from silanol-alcoholate/amide exchange resulting in the formation of bismuth carbon bonds. Their structures in the solid state reveal London dispersion type bismuth⋯π interactions that determine the supramolecular assemblies. Abstract : The alkoxide Bi[OCMe2 (2-C4 H3 S)]3 (1 ) is formed by the reaction of three equiv. of the alcohol HOCMe2 (2-C4 H3 S) with Bi(O t Bu)3 and subsequent hydrolysis provides the bismuth oxido cluster [Bi4 O2 {OCMe2 (2-C4 H3 S)}8 ] (2 ). In contrast, the reaction of Bi(O t Bu)3 and Bi[N(SiMe3 )2 ]3 with the silanols HOSiMe2 (2-C4 H3 X) (X = O, S, Se, and NMe), HOSiMe2 (2-C4 H2 S-5-SiMe3 ) and HOSiMe2 (3-C4 H3 S) leads to the formation of tris(heteroaryl)bismuthines Bi(2-C4 H2 X-5-R)3 [where X = O, R = H (3 ); X = S, R = H (4 ); X = S, R = SiMe3 (5 ); X = NMe, R = H (6 ); X = Se, R = H (7 )] and Bi(3-C4 H3 S)3 (8 ). For the silanols, bismuth–carbon bond formation is observed rather than silanol–alcoholate or silanol–amide exchange. The structures of compounds1, 2, and4–7a in the solid state were established by single crystal X-ray diffraction and all compounds except5 show London dispersion type bismuth⋯π heteroarene interactions. For the bismuthine Bi(2-C4 H3 Se)3 (7 ), two polymorphs were isolated depending on the conditions of crystallization. At 8 °C, polymorph I (7a ) crystallizes from an n -hexane solution in the triclinic space group P 1̄, whereas polymorph II (7b ) crystallizes at 20 °C from a CH2 Cl2 / n -pentane solution in the monoclinic space group P 21 / c . The heteroaryl bismuthines3 and4 exhibit 2D network structures as a result of bismuth⋯π heteroarene interactions, whereas for the pyrrole derivative6 the dispersion type interactions provide separated dimers.